Sinergi TNI-POLRI Untuk Menangkal Paham Radikalisme di Indonesia: Studi Kasus Kota Depok - Rumbiak, Alredo Agustinus; Gabriel J, Thomas; Novalino, Djoko Andreas (CV. Rayyan Dwi Bharata, 2025)
Depok, with its diverse population and unique socio-demographic characteristics, presents distinct challenges in countering the spread of radical ideologies. This city is particularly vulnerable to the influence of radicalism due to its complex social dynamics and the diverse interactions within its community. To maintain stability and prevent the proliferation of radicalism, strengthening the collaboration between the Indonesian National Armed Forces (TNI) and the Indonesian National Police (Polri) is a strategic necessity. Specifically, the synergy between Polres Metro Depok and Kodim 0508/Depok plays a vital role in fostering a conducive environment and enhancing vigilance against the threat of extremist ideologies. This article evaluates the synergy between TNI and Polri in Depok in countering radicalism through theoretical frameworks such as the TNIPolri-People Synergy Theory, Communication and Social Media Theory, and Radicalism Prevention Theory. A qualitative research method, including in- depth interviews, field observations, and literature reviews, was employed to gain a comprehensive understanding of the current collaborative practices. The findings reveal that while the collabor ation between TNI and Polri in Depok is established, there remains room for improvement to enhance the effectiveness of radicalism prevention measures. This research aims to provide strategic recommendations to strengthen TNI-Polri collaboration, particularly in early detection and prevention through the utilization of information technology, community-based outreach programs, and the reinforcement of the roles of Babinsa and Bhabinkamtibmas. The proposed model is expected to not only be applicable in Depok but also serve as a reference for other cities across Indonesia in addressing similar threats.